Influence of Electronic Word of Mouth on Consumer Purchase Intentions: A Brand Image Perspective - Dinar, Anisa Mesa; Solihat, Asri (Entrepreneurship Faculty, Universitas Garut, 2024)
This research is intended to test the influence of electronic word of mouth (E-WOM) on online purchase intention through brand image. The population in the research is potential luxury crime consumers with an unknown population size. This type of research is quantitative research which is included in the category of non-experimental research or survey with a correlational approach. The sample used in this research was 96 respondents who were distributed using offline and on line questionnaire which were then processed using SPSS software to test the validity and reliability of the instrument as well as SmartPLS software to carry out data analysis. The analysis used in this research is the outer model and inner model. The aim of this research is to determine the influence of E-WOM on on line purchase intention, the influence of E-WOM on brand image, the influence of brand image on online purchasing interest and finally the influence of E-WOM on online purchase intention through brand image. The research results show that E-WOM has an influence on online purchase intention by 65.6%, E-WOM has an influence on brand image by 24%, brand image has an influence on online purchase intention by 24% and E-WOM has an influence on online purchase intention through brand image by 6.8%.